Clad steel sheet, welded joint and method for manufacturing the same

CN122892964APending Publication Date: 2026-10-09JFE STEEL CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202580018758.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-03-12
Filing Date
2025-03-07
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

另外,已知氨SCC也会发生在焊接热影响部

Benefits of technology

[0049][4]一种焊接接头的制造方法,使用上述[1]所述的包层钢板,在热输入为50kJ/cm以下的条件下进行焊接,由此制造焊接接头。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

Provided is a high-strength clad steel sheet, a welded joint, and a method for manufacturing the same, which are excellent in ammonia SCC resistance, low-temperature toughness, and jointability, and are suitable for use in a tank for transporting and storing liquid ammonia. The clad steel sheet has a base material having a prescribed chemical composition, and a clad material having a prescribed chemical composition joined to at least one surface (a surface that becomes an inner surface), in which the base material has a tensile strength of 780 MPa or more, an absorbed energy in a Charpy impact test at -40°C of 47 J or more, and a jointability of the base material to the clad material of 70% or more.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a high-strength cladding steel sheet with excellent low-temperature toughness and resistance to stress corrosion cracking, and to welded joints obtained using this high-strength cladding steel sheet. Particularly, it relates to a high-strength cladding steel sheet suitable for structural components such as tanks used in liquid ammonia environments, and to welded joints obtained using this high-strength cladding steel sheet. Furthermore, it also relates to a method for manufacturing this high-strength cladding steel sheet and the welded joint. Background Technology

[0002] In a liquid ammonia environment, carbon steel may develop stress corrosion cracking (hereinafter referred to as ammonia SCC) caused by liquid ammonia. Therefore, for carbon steel structures such as piping, storage tanks, tank trucks, and pipelines used for handling liquid ammonia, measures have been taken to use steels with low susceptibility to ammonia SCC and to suppress ammonia SCC in operational settings.

[0003] For example, it is known that ammonia SCC is correlated with the strength and hardness of a material. When using carbon steel, materials with a tensile strength of less than 600 MPa are preferred. Furthermore, it is known that ammonia SCC can also occur in the weld heat-affected zone. Therefore, when using high-strength steel in a liquid ammonia environment, it is necessary to implement post-weld heat treatment based on overall annealing to adjust tensile strength, weld hardness, and other properties.

[0004] In recent years, liquid ammonia has attracted attention as a clean energy source because it does not produce CO2 even when burned, and large-scale demand is expected. Consequently, there is a need for larger-scale equipment for transporting and storing liquid ammonia.

[0005] Typically, when increasing the size of tanks, the aim is to reduce the weight and construction costs by using thinner steel, thus hoping to use high-strength steel.

[0006] In addition, for efficient use of the conveying and storage equipment, it is sometimes used for both liquid ammonia and LPG. Since liquefied gases such as liquid ammonia and LPG are conveyed or stored at low temperatures, the steel plates used for this purpose require excellent low-temperature toughness.

[0007] As a method that balances high strength with excellent resistance to ammonia SCC, Patent Document 1 is disclosed. Patent Document 1 describes a method for softening the surface of steel.

[0008] Existing technical documents

[0009] Patent documents

[0010] Patent Document 1: Japanese Patent Publication No. 55-30062 Summary of the Invention

[0011] However, in the method described in Patent Document 1, a long heat treatment is required to achieve uniform and sufficient softening of the surface layer, making it difficult to control the strength at the center of the steel plate. Therefore, there is a problem with the strength of the steel plate.

[0012] The purpose of this invention is to solve the above-mentioned problems and provide a high-strength cladding steel plate, welded joint, and manufacturing method thereof that are suitable for use in tanks for conveying and storing liquid ammonia and have excellent resistance to SCC, low-temperature toughness, and bonding properties.

[0013] Here, the following steps are used to determine whether the ammonia SCC resistance is excellent.

[0014] The cladding steel sheet of this invention is used in a manner where the cladding material comes into contact with ammonia, etc. Therefore, firstly, a thickness reduction process is performed on the base material side of the cladding steel sheet, and test pieces with a thickness of 1.5–3.0 mm × 15 mm × 115 mm are collected from the cladding material portion. When the cladding material thickness exceeds 3.0 mm, a test piece with a thickness of 3.0 mm is collected from the side of the cladding material that is not bonded to the base material. The collected test pieces are subjected to ultrasonic degreasing in acetone for 5 minutes. A stress of 100% of the actual yield strength YS of the base material corresponding to each test piece is applied to each test piece by four-point bending. The four-point bent test piece is placed in a test tank. Next, a solution of ammonium carbamate (5.00 mass%), O2 (1.000 bar), and water (0.10 mass%) mixed in 2 L of liquid ammonia with a purity of 99.999% or higher is filled into the test tank. Specifically, a specified amount of ammonium carbamate and water were added to the test tank, followed by the introduction of O2 gas and then liquid ammonia. The ratio of the impregnation liquid volume to the surface area of ​​the test piece, i.e., the specific liquid volume, was 42 mL / cm². Stirring during the test was performed continuously at 10 rpm using a stir bar located within the test tank. The test liquid temperature was set to 25°C. After adjusting the test liquid temperature to 25°C, the corrosion potential of the test piece was measured using a potentiostat. The potential measurement and application using the potentiostat were performed using a three-electrode method, with platinum electrodes used for both the reference and counter electrodes. One hour after the start of the corrosion potential measurement, it was determined that the potential had stabilized. At this point, control was implemented, applying a potential of +0.5V vs. Pt to the test piece to begin the impregnation test. After 504 hours from the start of the impregnation test, the test piece was removed from the test tank. Corrosion products on the surface of the test piece were removed, and cracks were visually observed on the surface and cross-section to evaluate the cracks. In this invention, for one condition, nine test pieces were used to conduct a 504-hour impregnation test. If two or fewer test pieces show cracks deeper than 1.5 mm, the ammonia SCC resistance is considered good (○), i.e., excellent; if three or more test pieces show cracks, the ammonia SCC resistance is considered poor (×).

[0015] In addition, excellent low-temperature toughness means that the energy absorbed during the Charpy impact test at -40℃ is above 47J, according to JIS Z 2242 (2023).

[0016] In addition, excellent bonding means that the bonding rate, expressed by the following formula, is 70% or higher in a cross section containing the base material and the cladding material.

[0017] Bonding rate (%): 100 × bonding interface length (mm) / total measurement length (mm)

[0018] In addition, high strength refers to the tensile strength (TS) of the base material, measured according to JIS Z 2241 (2022), being 780 MPa or higher.

[0019] To achieve the above objectives, the inventors conducted in-depth research on various factors affecting the ammonia SCC resistance, low-temperature toughness, and strength properties of steel plates. The results yielded the following insights.

[0020] That is, since ammonia SCC occurs on the inside of the product (can), the resistance to ammonia SCC is mainly determined by the surface properties of the steel plate that forms the inside. Therefore, it was conceived to use a steel plate with excellent strength and low-temperature toughness as the base material, and then to bond a cladding steel plate with excellent ammonia SCC resistance as the cladding material to the aforementioned base material.

[0021] Furthermore, it was found that by using this cladding steel plate, excellent values ​​could be obtained for ammonia SCC resistance, low-temperature toughness, and strength properties.

[0022] It should be noted that the cladding material used in this invention is stainless steel, which has superior corrosion resistance compared to cladding steel plates using carbon steel as the cladding material.

[0023] This invention is based on the above insights, that is, the main points of this invention are as follows.

[0024] [1] A cladding steel plate having a cladding material on at least one side of a base material,

[0025] The chemical composition of the aforementioned base material, by mass%, contains: C: 0.030–0.150%, Si: 0.05–0.55%, Mn: 0.50–2.10%, P: less than 0.020%, S: less than 0.010%, Al: 0.018–0.070%, Ni: 0.30–2.20%, Ti: 0.005–0.020%, N: 0.0020–0.0080%, O (oxygen): less than 0.0050%, and the Ti / N ratio is 2.2–6.5.

[0026] It further contains one or more of the following: Cu: less than 0.50%, Cr: less than 1.60%, Mo: less than 0.60%, Nb: less than 0.030%, V: less than 0.100%, B: less than 0.0050%, and Ca: less than 0.0040%, with the remainder consisting of Fe and unavoidable impurities.

[0027] Among the above-mentioned coating materials,

[0028] The PRE value shown in equation (1) is 15 or higher.

[0029] The tensile strength of the base material is above 780 MPa.

[0030] The base material absorbs over 47 J of energy in a Charpy impact test at -40°C.

[0031] The bonding rate between the base material and the coating material is over 70%.

[0032] PRE=Cr%+3.3Mo%+30N%-Mn%···(1)

[0033] In formula (1), M% represents the content (mass%) of element M in the coating material, and elements that are not present are set to 0 (zero).

[0034] [2] A welded joint is a welded joint using the cladding steel plate described in [1] above.

[0035] The heat-affected zone of the weld absorbs more than 47 J of energy in a Charpy impact test at -40°C.

[0036] [3] A method for manufacturing a cladding steel plate is the method for manufacturing a cladding steel plate described in [1] above.

[0037] The base material slab is heated to 900℃~1200℃ (surface temperature gauge) and then hot-rolled to a rolling finish temperature of 700℃ or higher (surface temperature gauge) to produce the base material slab.

[0038] After heating the slab blank of the coating material, hot rolling is performed to produce the coating material blank.

[0039] The laminated slab, formed by stacking the aforementioned base material blank and the aforementioned cladding material blank, is heated to 1000°C to 1250°C (surface temperature).

[0040] Hot rolling with a cumulative reduction rate of 65% or more and a rolling end temperature above the Ar3 phase transformation point and below 1000℃ is carried out to manufacture rolled plates with base material and cladding material.

[0041] The above-mentioned rolled plate is subjected to the following treatment (A) or (B).

[0042] (A)

[0043] After the hot-rolled plate is cooled,

[0044] Reheat to 800℃~1000℃,

[0045] Accelerated cooling is performed from a temperature above the Ar3 phase transition point of the base material at an average cooling rate ranging from 1.0℃ / s to 20.0℃ / s, down to a cooling stop temperature below 350℃.

[0046] After the above-mentioned accelerated cooling, tempering is carried out at a temperature of 550℃~700℃;

[0047] (B)

[0048] The hot-rolled plate is accelerated from a temperature above the Ar3 phase transformation point of the base material to a cooling stop temperature below 500°C at an average cooling rate of 3°C / s to 50°C / s, or further tempered at a temperature below 700°C after the above-mentioned accelerated cooling.

[0049] [4] A method for manufacturing a welded joint, wherein the cladding steel plate described in [1] is used to weld the joint under a heat input of less than 50 kJ / cm, thereby manufacturing the welded joint.

[0050] According to the present invention, a high-strength cladding steel plate suitable for use in structural components such as tanks in liquid ammonia environments can be provided, exhibiting excellent resistance to ammonia SCC, low-temperature toughness, and bonding properties. Detailed Implementation

[0051] The present invention relates to a cladding steel sheet having a cladding material as a corrosion-resistant alloy on at least one side of a base material. That is, the cladding steel sheet of the present invention has a base material and a cladding material formed on at least one side of the base material.

[0052] Here, because of the excellent resistance to ammonia SCC and low-temperature toughness of the present invention, it is suitable for structural components such as tanks used in liquid ammonia environments. However, the above environment is not limited to liquid ammonia, but can also be other liquefied gases such as LPG and liquefied CO2.

[0053] In this invention, the surface having the aforementioned cladding material can be any side of the base material, but when used as a cladding steel sheet, it must be at least the side in contact with ammonia, etc. This is because the ammonia SCC resistance and low-temperature toughness of this invention can be obtained. It should be noted that in this invention, the surface in contact with ammonia, etc., is also referred to as the inner surface. Furthermore, it is not limited to an assembled slab (laminated slab) produced by stacking a base material slab (the blank of the base steel sheet) and a cladding material slab (the blank of the cladding material steel sheet). For example, it can also be a method of producing an assembled slab by adding elements to one or two sides of the base material slab in a gas atmosphere to form the chemical composition of the cladding material.

[0054] The embodiments of the present invention will be described in further detail below.

[0055] The cladding steel sheet of the present invention is a cladding steel sheet having a coating material on at least one side of a base material. The chemical composition of the base material, in mass percent, contains C: 0.030-0.150%, Si: 0.05-0.55%, Mn: 0.50-2.10%, P: less than 0.020%, S: less than 0.010%, Al: 0.018-0.070%, Ni: 0.30-2.20%, Ti: 0.005-0.020%, N: 0.0020-0.0080%, O (oxygen): less than 0.0050%, and the Ti / N ratio is 2.2-6.5.

[0056] It further contains one or more of the following: Cu: less than 0.50%, Cr: less than 1.60%, Mo: less than 0.60%, Nb: less than 0.030%, V: less than 0.100%, B: less than 0.0050%, and Ca: less than 0.0040%, with the remainder consisting of Fe and unavoidable impurities.

[0057] In coating materials, the PRE value shown by formula (1) is 15 or higher.

[0058] The tensile strength of the base material is above 780 MPa, the energy absorbed by the base material in the Charpy impact test at -40℃ is above 47 J, and the bonding rate between the base material and the coating material is above 70%.

[0059] PRE=Cr%+3.3Mo%+30N%-Mn%···(1)

[0060] In formula (1), M% represents the content (mass%) of element M in the coating material, and elements that are not present are set to 0 (zero).

[0061] It should be noted that unless otherwise specified, the "%" indicating the content of the constituent elements refers to "mass %".

[0062] (1) Chemical composition of the parent material

[0063] C: 0.030~0.150%

[0064] Carbon (C) is the most effective element for increasing the strength of steel sheets manufactured by cooling according to the present invention. To achieve this effect, the C content is specified to be 0.030% or more. Furthermore, from the viewpoint of reducing the content of other alloying elements and manufacturing at a lower cost, the C content is preferably 0.040% or more, and more preferably 0.050% or more.

[0065] On the other hand, a carbon content exceeding 0.150% leads to a deterioration in the toughness and weldability of the steel plate. Therefore, the carbon content is specified to be 0.150% or less. Furthermore, from the viewpoint of toughness, the carbon content is preferably 0.140% or less, and more preferably 0.130% or less.

[0066] Si: 0.05–0.55%

[0067] In addition to increasing the strength of the steel sheet, silicon (Si) is added for deoxidation. To achieve this effect, the Si content is specified to be 0.05% or more. Furthermore, the Si content is preferably 0.07% or more, and more preferably 0.10% or more.

[0068] On the other hand, a Si content exceeding 0.55% leads to a deterioration in toughness and weldability. Therefore, the Si content is specified to be 0.55% or less. Furthermore, the Si content is preferably 0.50% or less, and more preferably 0.40% or less.

[0069] Mn: 0.50~2.10%

[0070] Mn is an element that improves the hardenability of steel and is one of the essential elements required to achieve the high strength required by this invention. To obtain this effect, the Mn content is specified to be 0.50% or more. Furthermore, from the viewpoint of reducing the content of other alloying elements and manufacturing at a lower cost, the Mn content is preferably 0.70% or more.

[0071] On the other hand, a Mn content exceeding 2.10% leads to deterioration in weldability. Therefore, the Mn content is specified to be 2.10% or less. Furthermore, the Mn content is preferably 1.90% or less.

[0072] P: below 0.020%

[0073] Phosphorus (P) is an unavoidable impurity element that causes adverse effects such as reduced toughness and weldability due to segregation at grain boundaries. Therefore, it is preferable to minimize the P content as much as possible, but it is acceptable if it is below 0.020%. Furthermore, the P content is preferably below 0.015%.

[0074] It should be noted that there is no particular limit to the lower limit of P content, which can be 0%, but P is usually an element that is inevitably present in steel as an impurity, so it can exceed 0% in industrial applications. In addition, excessive reduction will lead to an increase in refining costs, so the P content is preferably 0.001% or more, and more preferably 0.003% or more.

[0075] S: below 0.010%

[0076] Sulfur (S) is an unavoidable impurity element. It exists in steel as sulfide inclusions such as MnS, creating fracture initiation points and reducing the toughness of the steel plate, thus having a negative impact. Therefore, it is preferable to minimize the S content as much as possible, but 0.010% or less is acceptable. Furthermore, the S content is preferably 0.005% or less, and more preferably 0.003% or less.

[0077] It should be noted that there is no specific lower limit for the sulfur content, which can be 0%. However, sulfur is usually an element that is unavoidably present in steel as an impurity, so in industrial applications, it can exceed 0%. In addition, excessive reduction will lead to an increase in refining costs, so from a cost point of view, the sulfur content is preferably 0.001% or higher.

[0078] Al: 0.018~0.070%

[0079] Al acts as a deoxidizer. To achieve this effect, the Al content is specified to be 0.018% or more. Furthermore, the Al content is preferably 0.025% or more.

[0080] On the other hand, if the Al content exceeds 0.070%, oxide inclusions increase, cleanliness decreases, and toughness also decreases. Therefore, the Al content is specified to be 0.070% or less. Furthermore, from the viewpoint of preventing toughness degradation, the Al content is preferably 0.060% or less, and more preferably 0.050% or more.

[0081] Ni: 0.30~2.20%

[0082] Ni is effective not only in improving the strength of steel plates but also in improving the toughness of the base metal and the heat-affected zone of welds. However, when the Ni content is less than 0.30%, this effect is insufficient, and when it exceeds 2.20%, defects occur on the surface of the steel plate. Therefore, the Ni content is specified to be in the range of 0.30% to 2.20%. Furthermore, the Ni content is preferably 0.60% or more, more preferably 0.70% or more. Additionally, the Ni content is preferably 2.10% or less, more preferably 1.80% or less, and even more preferably 1.50% or less.

[0083] Ti: 0.005~0.020%

[0084] Ti is an element with a strong tendency to form nitrides and has the effect of fixing nitrogen and reducing dissolved nitrogen. Therefore, adding Ti can improve the toughness of the weld. To achieve this effect, the Ti content needs to be set to 0.005% or higher.

[0085] On the other hand, if the Ti content exceeds 0.020%, the toughness decreases. Therefore, the Ti content is specified to be in the range of 0.005% to 0.020%. Furthermore, the Ti content is preferably 0.008% or more. Additionally, the Ti content is preferably ~0.017% or less.

[0086] N: 0.0020~0.0080%

[0087] Nitrogen (N) can improve the toughness of the weld by forming TiN. To achieve this effect, the N content needs to be set to 0.0020% or higher.

[0088] On the other hand, if the nitrogen content exceeds 0.0080%, the toughness decreases. Therefore, the nitrogen content is specified to be in the range of 0.0020% to 0.0080%. Furthermore, the nitrogen content is preferably 0.0025% or more. In addition, the nitrogen content is preferably 0.0070% or less, more preferably 0.0060% or less, and even more preferably 0.0050% or less.

[0089] O (Oxygen): below 0.0050%

[0090] O is an element that is unavoidably present as an impurity in steel, existing as oxides such as Al2O3. It is an element that can cause fracture initiation points and reduce the toughness of the steel sheet, among other adverse effects. Therefore, it is preferable to minimize the O content as much as possible, but 0.0050% or less is acceptable. Furthermore, the O content is preferably 0.0040% or less, and more preferably 0.0030% or less.

[0091] It should be noted that there is no particular limit to the lower limit of the O content, which can be 0%. However, O is usually an element that is inevitably present in steel as an impurity, so it can exceed 0% in industrial applications. In addition, excessive reduction will lead to an increase in refining costs. Therefore, from a cost point of view, the O content is preferably 0.0005% or more, and more preferably 0.0010% or more.

[0092] Ti / N: 2.2–6.5

[0093] The formation of TiN can improve the toughness of the weld. To achieve this effect, the relationship between Ti and N content becomes important. When the Ti / N ratio is less than 2.2 or more than 6.5, the grains become coarser and the toughness deteriorates. Therefore, the Ti / N ratio is specified to be in the range of 2.2 to 6.5. Furthermore, the Ti / N ratio is preferably 2.3 or more. In addition, the Ti / N ratio is preferably 3.9 or less, and more preferably 3.8 or less.

[0094] In addition to the components described above, the raw material of this invention may further contain one or more of the elements listed below, with the remainder being Fe and unavoidable impurities. Unavoidable impurities refer to impurities that are unavoidably introduced from raw materials, manufacturing processes, or manufacturing equipment, and are permitted to be present to a extent that does not hinder the purpose of this invention. Examples of raw materials include iron ore, reduced iron, and scrap steel. Examples of impurities include, for example, Co, Sn, Zn, Pb, As, Sb, Bi, H, and REM.

[0095] Cu: below 0.50%

[0096] Cu is an effective element for improving the strength of steel plates. However, when the Cu content is less than 0.05%, this effect is insufficient. Therefore, the Cu content is preferably 0.05% or more. Furthermore, the Cu content is more preferably 0.10% or more, and even more preferably 0.15% or more.

[0097] On the other hand, if the Cu content exceeds 0.50%, defects will occur on the surface of the steel plate. Therefore, in the case of Cu content, the Cu content is set to 0.50% or less. The Cu content is preferably 0.45% or less, and more preferably 0.40% or less.

[0098] Cr: below 1.60%

[0099] Cr is an effective element for improving the strength of steel plates. However, when the Cr content is less than 0.05%, this effect is insufficient. Therefore, the Cr content is preferably 0.05% or more. Furthermore, the Cr content is preferably 0.10% or more.

[0100] On the other hand, if the Cr content exceeds 1.60%, the toughness of the steel plate deteriorates. Therefore, in cases where Cr is present, the Cr content is specified to be 1.60% or less. The Cr content is preferably 1.50% or less, and more preferably 1.40% or less.

[0101] Mo: 0.60% or less

[0102] Mo is an effective element for improving the strength of steel plates. However, when the Mo content is less than 0.05%, this effect is insufficient. Therefore, the Mo content is preferably 0.05% or more. Furthermore, the Mo content is preferably 0.10% or more.

[0103] On the other hand, if the Mo content exceeds 0.60%, the toughness of the steel plate deteriorates. Therefore, when Mo is present, the Mo content is set to 0.60% or less. Preferably, the Mo content is 0.55% or less.

[0104] Nb: below 0.030%

[0105] Nitrogen (Nb) is an element that reduces the original austenite grain size and improves toughness by precipitating as carbonitrides. To achieve this effect, the Nb content is preferably 0.005% or more. Furthermore, the Nb content is more preferably 0.007% or more.

[0106] On the other hand, if the Nb content exceeds 0.030%, a large amount of NbC will precipitate, reducing toughness. Therefore, when Nb is present, the Nb content is set to 0.030% or less. Furthermore, the Nb content is preferably 0.027% or less, and more preferably 0.025% or less.

[0107] V: Below 0.100%

[0108] V is an effective element for improving the strength of steel plates. However, when the V content is less than 0.005%, this effect is insufficient. Therefore, the V content is preferably 0.005% or more. Furthermore, the V content is preferably 0.030% or more.

[0109] On the other hand, if the V content exceeds 0.100%, the toughness of the steel plate deteriorates. Therefore, when V is present, the V content is set to 0.100% or less. The V content is preferably 0.080% or less, and more preferably 0.050% or less.

[0110] B: Below 0.0050%

[0111] Boron (B) is an effective element for improving the strength of steel plates. However, when the B content is less than 0.0005%, this effect is insufficient. Therefore, the B content is preferably 0.0005% or more. Furthermore, the B content is preferably 0.0008% or more.

[0112] On the other hand, if the boron content exceeds 0.0050%, the toughness of the steel plate deteriorates. Therefore, when boron is present, the boron content is set to 0.0050% or less. The boron content is preferably 0.0040% or less, and more preferably 0.0030% or less.

[0113] Ca: below 0.0040%

[0114] Ca is an element that combines with S and inhibits the formation of MnS and other inclusions that elongate along the rolling direction. In other words, by including Ca, the morphology of sulfide inclusions is controlled to be spherical, which improves the toughness of welds and the like. To achieve this effect, the Ca content is preferably 0.0005% or more. The Ca content is preferably 0.0010% or more.

[0115] On the other hand, if the Ca content exceeds 0.0040%, the cleanliness of the steel decreases. Therefore, in the case of Ca content, the Ca content is set to 0.0040% or less. The Ca content is preferably 0.0030% or less.

[0116] (2) Coating material

[0117] PRE value: 15 or above

[0118] PRE=Cr%+3.3Mo%+30N%-Mn%···(1)

[0119] In formula (1), M% represents the content (mass%) of element M in the coating material.

[0120] PRE is the pitting corrosion resistance index, calculated as PRE = Cr% + 3.3Mo% + 30N% - Mn%. A higher PRE value indicates lower susceptibility to liquid ammonia SCC. Therefore, the PRE value of coating materials is specified to be 15 or higher.

[0121] On the other hand, a higher PRE value for the cladding material is better, but an excessively high PRE value will lead to increased costs. Therefore, a PRE value of 55 or less is preferred, and more preferably 27 or less. The cladding material is preferably stainless steel. The microstructure of the stainless steel is not limited, but from the viewpoint of improving the toughness of the weld heat-affected zone in the cladding material, austenitic stainless steel or duplex stainless steel is preferred. The cladding material may also be a Ni-based alloy.

[0122] The chemical composition of the aforementioned coating material is not particularly limited as long as the PRE value is 15 or higher. However, more specifically, the chemical composition of the aforementioned coating material preferably contains, by mass%, C: 0.001-0.080%, Si: 0.05-1.00%, Mn: 0.30-4.00%, P: less than 0.045%, S: less than 0.030%, Ni: 0.05-80.0%, Cr: 11.0-28.0%, N: 0.005-0.400%, O (oxygen): less than 0.0050%, with the remainder consisting of Fe and unavoidable impurities.

[0123] In addition, the chemical composition of the above-mentioned coating material may further include Cu: less than 3.00%, Mo: less than 5.50%, V: less than 0.100%, Nb: less than 3.00%, Ti: less than 1.00%, B: less than 0.0050%, Ca: less than 0.0040%, Al: less than 0.50%, Co: less than 1.20%, and Ta: less than 3.00%, as needed.

[0124] The embodiments of the present invention will be described in detail below.

[0125] C: 0.001~0.080%

[0126] Carbon (C) is the most effective element for increasing the strength of steel sheets manufactured by cooling according to the present invention. To achieve this effect, the C content is preferably 0.001% or more. Furthermore, from the viewpoint of reducing the content of other alloying elements and manufacturing at a lower cost, the C content is more preferably 0.010% or more.

[0127] On the other hand, if the carbon content exceeds 0.080%, carbides precipitate at grain boundaries, sometimes leading to stress corrosion cracking upon contact with liquid ammonia. Therefore, the carbon content is preferably 0.080% or less. Furthermore, from a toughness perspective, the carbon content is more preferably 0.050% or less.

[0128] Si: 0.05~1.00%

[0129] In addition to increasing the strength of the steel sheet, silicon (Si) is added for deoxidation. To achieve this effect, the Si content is preferably 0.05% or more. Furthermore, the Si content is more preferably 0.07% or more.

[0130] On the other hand, if the Si content exceeds 1.00%, it can sometimes lead to a deterioration in toughness and weldability. Therefore, the Si content is preferably 1.00% or less. Furthermore, the Si content is more preferably 0.80% or less.

[0131] Mn: 0.30~4.00%

[0132] Besides improving the hardenability of steel, manganese (Mn) is also an important element that needs to be added for deoxidation. To achieve this effect, the Mn content is preferably 0.30% or more. Furthermore, from the viewpoint of reducing the content of other alloying elements and manufacturing at a lower cost, the Mn content is more preferably 0.40% or more.

[0133] On the other hand, if the Mn content exceeds 4.00%, it can sometimes lead to deterioration of weldability. Therefore, the Mn content is preferably 4.00% or less. Furthermore, the Mn content is more preferably 3.00% or less.

[0134] P: below 0.045%

[0135] Phosphorus (P) is an unavoidable impurity element that can cause adverse effects such as reduced toughness and weldability due to segregation at grain boundaries. Therefore, it is preferable to minimize the P content as much as possible, but a content of 0.045% or less is acceptable. A P content of 0.040% or less is more preferred.

[0136] Furthermore, there is no specific lower limit for the phosphorus (P) content; it can be 0%. However, P is usually an element that is unavoidably present in steel as an impurity, so industrially it can be 0% or higher. Additionally, excessive reduction will lead to increased refining costs; therefore, the P content is preferably 0.001% or higher.

[0137] S: below 0.030%

[0138] Sulfur (S) is an element present as an unavoidable impurity in steel. It exists as a sulfide inclusion in steel, such as MnS, and can potentially become a fracture initiation point, reducing the toughness of the steel plate and causing adverse effects. Therefore, it is preferable to minimize the S content as much as possible, but 0.030% or less is acceptable. A content of 0.025% or less is more preferable. Furthermore, there is no particular limitation on the lower limit of the S content; it can be 0%. However, since S is generally an element unavoidably present in steel as an impurity, it can be 0% or more industrially. Additionally, excessive reduction leads to increased refining costs; therefore, from a cost perspective, an S content of 0.001% or more is preferred.

[0139] Ni: 0.05~80.0%

[0140] Ni is an effective element for improving the corrosion resistance of stainless steel and Ni-based alloys to various acids. Furthermore, it is effective not only in increasing the strength of steel sheets but also in improving the toughness of the base metal and the heat-affected zone of welds. However, this effect is insufficient when the Ni content is less than 0.05%. Therefore, the Ni content is preferably 0.05% or more. Moreover, the Ni content is more preferably 0.10% or more.

[0141] On the other hand, Ni is an expensive metal, and from the viewpoint of alloy cost, the Ni content is preferably 80.0% or less. Furthermore, the Ni content is more preferably 46.0% or less. When stainless steel, rather than a Ni-based alloy, is used as the cladding material, the Ni content can be 25.0% or less, 20.0% or less, 13.0% or less, or 10.0% or less.

[0142] Cr: 11.0~28.0%

[0143] Cr is an effective element for improving the corrosion resistance of stainless steel. To prevent stress corrosion cracking upon contact with liquid ammonia, the Cr content is preferably 11.0% or more. Furthermore, the Cr content is more preferably 13.0% or more.

[0144] On the other hand, if the Cr content exceeds 28.0%, the toughness of duplex stainless steel and the corrosion resistance of welds may sometimes deteriorate. Therefore, the Cr content is preferably 28.0% or less. Furthermore, the Cr content is more preferably 26.0% or less.

[0145] N: 0.005~0.400%

[0146] Nitrogen (N) is an effective element for improving the corrosion resistance and strength of stainless steel. To achieve this effect, the N content is preferably 0.005% or more. Furthermore, the N content is more preferably 0.010% or more.

[0147] On the other hand, if the nitrogen content exceeds 0.400%, the toughness may sometimes decrease. Therefore, the nitrogen content is preferably 0.400% or less. Furthermore, the nitrogen content is more preferably 0.300% or less.

[0148] O (Oxygen): below 0.0050%

[0149] O (O) is an element present as an unavoidable impurity in steel. It exists in steel as oxides such as Al₂O₃, creating fracture initiation points and reducing the toughness of the steel sheet, thus having a negative impact. Therefore, it is preferable to minimize the O content as much as possible, but 0.0050% or less is acceptable. It should be noted that there is no particular lower limit to the O content; it can be 0%, but since O is generally an unavoidable impurity in steel, it can be 0% or more industrially. Furthermore, excessive reduction leads to increased refining costs; therefore, from a cost perspective, the O content is preferably 0.0005% or more.

[0150] In addition to the above-mentioned components, the coating material of this invention may further contain the following components as needed. The remaining portion consists of Fe and unavoidable impurities. Unavoidable impurities refer to impurities that are unavoidably introduced from raw materials, manufacturing processes, or manufacturing equipment, and are permitted to be present to a extent that does not hinder the purpose of this invention. Examples of raw materials include iron ore, reduced iron, and scrap steel. Examples of impurities include, for example, Sn, Zn, Pb, As, Sb, Bi, H, and REM.

[0151] Cu: below 3.00%

[0152] Cu is an effective element for improving the corrosion resistance and strength of steel plates. However, when the content is less than 0.05%, the effect is insufficient. Therefore, the Cu content is preferably 0.05% or more. Furthermore, the Cu content is more preferably 0.10% or more.

[0153] If the Cu content exceeds 3.00%, the hot workability may be significantly reduced. Therefore, when Cu is present, the Cu content is preferably in the range of 3.00% or less. Furthermore, the Cu content is more preferably 2.20% or less.

[0154] Mo: 5.50% or less

[0155] Mo is an effective element for improving the pitting corrosion resistance of stainless steel. However, when the content is less than 0.05%, the effect is insufficient. Therefore, when Mo is present, the Mo content is preferably 0.05% or more. Furthermore, the Mo content is more preferably 0.10% or more.

[0156] If the Mo content exceeds 5.50%, for example in the case of duplex stainless steel, the precipitation of the σ phase may be promoted depending on the cooling rate of the steel sheet, resulting in a significant deterioration in corrosion resistance. Therefore, in the case of Mo content, the Mo content is preferably 5.50% or less. Furthermore, the Mo content is more preferably 5.00% or less.

[0157] V: Below 0.100%

[0158] V combines with C more readily than Cr, thus it is an effective element for suppressing corrosion resistance degradation caused by Cr carbide formation. However, this effect is insufficient when the V content is less than 0.005%. Therefore, when V is present, the V content is preferably 0.005% or more. Furthermore, the V content is more preferably 0.010% or more.

[0159] On the other hand, from the viewpoint of alloy cost, when V is present, the V content is preferably 0.100% or less. Furthermore, the V content is more preferably 0.080% or less.

[0160] Nb: below 3.00%

[0161] Compared to Cr, Nb combines with C more readily, making it an effective element for suppressing corrosion resistance degradation caused by Cr carbide formation. However, this effect is insufficient at concentrations below 0.005%. Therefore, when Nb is present, the Nb content is preferably 0.005% or more. Furthermore, the Nb content is more preferably 0.010% or more.

[0162] On the other hand, from the viewpoint of alloy cost, when Nb is present, the Nb content is preferably 3.00% or less. Furthermore, the Nb content is more preferably 2.50% or less.

[0163] Ti: Below 1.00%

[0164] Ti combines with C more readily than Cr, making it an effective element for suppressing corrosion resistance degradation caused by Cr carbide formation. However, this effect is insufficient when the content is less than 0.01%. Therefore, when Ti is present, the Ti content is preferably 0.01% or more. Furthermore, the Ti content is more preferably 0.05% or more, and even more preferably 0.07% or more.

[0165] On the other hand, from the viewpoint of alloy cost, when Ti is present, the Ti content is preferably 1.00% or less. Furthermore, the Ti content is more preferably 0.90% or less.

[0166] B: Below 0.0050%

[0167] Boron (B) is an effective element for improving the strength of steel plates. However, when the B content is less than 0.0005%, this effect is insufficient. Therefore, when B is present, the B content is preferably 0.0005% or more. More preferably, the B content is 0.0008% or more.

[0168] If the boron content exceeds 0.0050%, the toughness of the steel plate may deteriorate. Therefore, when boron is present, the boron content is preferably 0.0050% or less. More preferably, the boron content is 0.0040% or less.

[0169] Ca: below 0.0040%

[0170] Ca is an element that combines with S and inhibits the formation of MnS and other substances that elongate along the rolling direction. That is, by containing Ca, sulfide inclusions are morphologically controlled to be spherical, which improves the toughness of welds and the like. To achieve this effect, when Ca is present, the Ca content is preferably 0.0005% or more. More preferably, the Ca content is 0.0010% or more.

[0171] On the other hand, if the Ca content exceeds 0.0040%, there is a concern that the cleanliness of the steel may be reduced. Therefore, when Ca is present, the Ca content is preferably 0.0040% or less. More preferably, the Ca content is 0.0030% or less.

[0172] Al: below 0.50%

[0173] Al is an effective deoxidizing element. This effect is fully realized when the Al content is 0.02% or higher; therefore, in the case of Al content, the Al content is preferably 0.02% or higher. However, when the Al content exceeds 0.50%, resistance to stress corrosion cracking decreases. Therefore, in the case of Al content, the Al content is preferably 0.50% or less, more preferably 0.30% or less.

[0174] Co: below 1.20%

[0175] Co is also an element that improves corrosion resistance, and this effect is achieved by containing 0.01% or more. Therefore, the Co content is preferably 0.01% or more. However, if the content exceeds 1.20%, the alloy price increases. Therefore, when Co is present, the Co content is preferably 1.20% or less. The Co content is more preferably 0.05% or more. The Co content is more preferably 1.00% or less.

[0176] Ta: Below 3.00%

[0177] Ta is an element effective in fixing carbon. This effect is fully realized when Ta content is 0.02% or higher; therefore, when Ta is present, Ta content is preferably 0.02% or higher. On the other hand, when Ta is in excess, it forms low-melting-point intermetallic compounds, reducing hot workability. Therefore, when Ta is present, Ta content is preferably 3.00% or lower.

[0178] (3) Characteristics of cladding steel plate

[0179] [Tensile Strength]

[0180] The cladding steel sheet of the present invention is a steel sheet having a tensile strength of 780 MPa or higher than that of the base material. There is no particular upper limit to the tensile strength, but the tensile strength of the high-strength steel sheet of the present invention can be 1000 MPa or less.

[0181] [Energy absorbed in the Charpy impact test]

[0182] In the cladding steel sheet of the present invention, the energy absorbed by the base material in a Charpy impact test at -40°C is 47 J or more. When used as a structural component such as a tank, PWHT (Post Weld Heat Treatment) is performed, but it may not be performed depending on the sheet thickness. In this case, the required energy absorption of the base material is higher, so it is preferably 100 J or more, and more preferably 170 J or more.

[0183] [Joint ratio]

[0184] In cladding steel sheets, there are regions where the base material and the cladding material are separated by oxides or voids, and regions where the base material and the cladding material are directly bonded. The bond strength between the base material and the oxides, and the bond strength between the cladding material and the oxides, are both less than the bond strength between the base material and the cladding material. Therefore, the higher the bonding rate between the base material and the cladding material, the higher the bond strength of the cladding steel sheet, and the lower the likelihood of peeling problems during product processing. In the cladding steel sheet of the present invention, the bonding rate between the base material and the cladding material is 70% or more. The bonding rate between the base material and the cladding material is preferably 80% or more, more preferably 85% or more. There is no particular upper limit to the bonding rate between the base material and the cladding material; the higher the better, and it can also be 100%.

[0185] [Panel thickness, overlay ratio]

[0186] The cladding steel plate of the present invention is not particularly limited, and its thickness can be 7 mm or more. Preferably, the thickness of the cladding steel plate of the present invention is 18 mm or more, more preferably 23 mm or more. Furthermore, the thickness of the cladding steel plate of the present invention can be 66 mm or less. Preferably, the thickness of the cladding steel plate of the present invention is 53 mm or less, more preferably 48 mm or less, and even more preferably 41 mm or less.

[0187] Furthermore, the thickness of the base material of the cladding steel sheet of the present invention can be 6 mm or more. The thickness of the base material of the cladding steel sheet of the present invention is preferably 15 mm or more, more preferably 20 mm or more. The thickness of the base material of the cladding steel sheet of the present invention can be 60 mm or less. The thickness of the base material is preferably 50 mm or less, more preferably 45 mm or less, and even more preferably 38 mm or less.

[0188] Furthermore, the thickness of the cladding material of the cladding steel sheet of the present invention can be 1.0 mm or more. The thickness of the cladding material of the cladding steel sheet of the present invention is preferably 2.0 mm or more, more preferably 2.5 mm or more. The thickness of the cladding material of the cladding steel sheet of the present invention can be 6.0 mm or less. The thickness of the cladding material of the cladding steel sheet of the present invention is preferably 5.0 mm or less, more preferably 4.0 mm or less.

[0189] The cladding steel plate of the present invention is not particularly limited, and the coverage ratio can be 0.01 or more. The coverage ratio of the cladding steel plate of the present invention is preferably 0.03 or more, more preferably 0.05 or more. The cladding steel plate of the present invention is not particularly limited, and the coverage ratio can be 0.50 or less. The coverage ratio of the cladding steel plate of the present invention is preferably 0.40 or less, more preferably 0.30 or less.

[0190] (4) Welded joint

[0191] In this invention, the aforementioned cladding steel plates are welded to manufacture structures such as tanks. There are no particular limitations on the type of welding; conventionally known steel plate welding methods can be used, with TIG welding being preferred.

[0192] In welded joints, the energy absorbed by the heat-affected zone in a Charpy impact test at -40°C is preferably 47 J or more.

[0193] [Heat input: below 50kJ / cm]

[0194] When manufacturing welded joints using the cladding steel plate of the present invention, the heat input is specified to be 50 kJ / cm or less. Furthermore, the heat input is preferably 30 kJ / cm or less. More preferably, it is 20 kJ / cm or less. By satisfying this heat input range, the aforementioned characteristics can be achieved. The lower limit of the heat input is not particularly limited, but excessive reduction will lead to a decrease in welding efficiency; therefore, the heat input is preferably 5.0 kJ / cm or more.

[0195] (5) Manufacturing conditions

[0196] In this invention, firstly, billets and slabs of the base material having the above-mentioned chemical composition and billets and slabs of the cladding material are manufactured. There are no particular limitations on the manufacturing method of these billets and slabs; conventionally known slab manufacturing methods can be used. That is, molten steel adjusted to the above-mentioned chemical composition is cast using a conventional casting method (converter method, electric furnace method, etc.) through a conventional casting method (continuous casting method, ingot casting method) to obtain the billets and slabs.

[0197] Next, the obtained base material slab is heated to 900°C–1200°C using a surface thermometer and then hot-rolled. The finishing temperature of the hot rolling is set to 700°C or higher using the surface thermometer, producing base material slabs of specified dimensions. Additionally, the obtained cladding material slab is heated and hot-rolled to produce cladding material slabs of specified dimensions.

[0198] [Heating temperature: 900℃~1200℃]

[0199] In the cladding steel sheet of the present invention, when the heating temperature of the blank of the base material is below 900°C, the solid solution of carbides is insufficient, and the required strength cannot be obtained. Therefore, the heating temperature is set to 900°C or higher using a surface thermometer. Furthermore, the heating temperature is preferably 920°C or higher.

[0200] On the other hand, energy consumption increases when the slab of the base material is heated to above 1200°C. Therefore, the heating temperature is set to 1200°C or below using a surface thermometer. The heating temperature is preferably 1150°C or below.

[0201] [Finishing Temperature (FT): Above 700℃]

[0202] If the rolling end temperature of the above-mentioned hot rolling is below 700°C, the generated ferrite is affected by the processing, thus deteriorating its toughness. Therefore, the rolling end temperature is set to 700°C or higher using a surface temperature gauge. Furthermore, the rolling end temperature is preferably 750°C or higher.

[0203] There is no particular upper limit, but the rolling end temperature, measured by surface temperature gauge, is preferably below 1000°C.

[0204] Next, the obtained base blank is overlapped with a cladding material blank on the side in contact with ammonia to form at least two layers, or the sacrificial material, cladding material blank and base blank are overlapped to form three layers, and the base blank, cladding material blank, cladding material blank and base blank are further overlapped to form a four-layer cladding blank, etc. The cladding blank is then pressed together and subjected to appropriate heat treatment for microstructure control.

[0205] It should be noted that, as a slab stacking method, in the table of the following embodiments, the method of stacking in the order of base material slab, cladding material slab, cladding material slab, and base material slab from top to bottom, or in the order of cladding material slab, base material slab, base material slab, and cladding material slab, is referred to as a sandwich method. Furthermore, the method of stacking in the order of cladding material slab and base material slab from top to bottom, or in the order of base material slab and cladding material slab, is referred to as an open method. Additionally, the method of stacking in the order of sacrificial material, cladding material slab, and base material slab from top to bottom, or in the order of base material slab, cladding material slab, and sacrificial material, is referred to as a sacrificial material method.

[0206] A cladding slab (laminated slab) formed by overlapping a base material slab and a cladding material slab is heated to a temperature range of 1000°C to 1250°C using a surface thermometer and then hot-rolled. In the hot rolling of this invention, the cumulative reduction rate is set to 65% or more, and the rolling end temperature is set to above the Ar3 phase transformation point and below 1000°C. Furthermore, after performing this hot rolling, the following treatment (A) or (B) is performed.

[0207] (A) After the hot-rolled plate is cooled, it is reheated to 800℃~1000℃ and accelerated to a cooling stop temperature below 350℃ from the temperature above the Ar3 phase transformation point of the base material at an average cooling rate of 1.0℃ / s~20.0℃ / s.

[0208] Next, the rolled plate is reheated to 800°C to 1000°C, for example at an average rate of 1°C / s to 50°C / s. After accelerated cooling, it is tempered at a temperature of 550°C to 700°C.

[0209] (B) The hot-rolled sheet is accelerated from a temperature above the Ar3 phase transformation point of the base material at an average cooling rate of 3°C / s to 50°C / s to a cooling stop temperature below 500°C. Alternatively, after accelerated cooling, it is further tempered at a temperature below 700°C.

[0210] [Heating temperature: 1000℃~1250℃]

[0211] When the heating temperature of the laminated slab formed by stacking the base material blank and the cladding material blank is below 1000°C, the solid solution of carbides is insufficient, and the required strength cannot be obtained. Furthermore, from the viewpoint of the bondability of the cladding steel, a high heating temperature is preferred. Therefore, the aforementioned heating temperature is set to 1000°C or higher. Moreover, the aforementioned heating temperature is preferably 1020°C or higher.

[0212] On the other hand, if the heating temperature exceeds 1250°C, energy consumption increases. Therefore, the heating temperature is set to 1250°C or lower. Furthermore, the heating temperature is preferably 1230°C or lower.

[0213] [Cumulative reduction rate of laminated slabs: 65% or more]

[0214] By rolling the laminated slab with a cumulative reduction rate of 65% or more, austenite recrystallization is promoted, and deformation bands that serve as nucleation sites are introduced into the austenite grains. This refines the bainite and martensite generated during the subsequent accelerated cooling under the conditions described later, thereby improving the toughness of the cladding steel sheet. Therefore, the cumulative reduction rate of the laminated slab is set to 65% or more. Preferably, the cumulative reduction rate of the laminated slab is 70% or more. It should be noted that there is no particular upper limit to the cumulative reduction rate of the laminated slab, but from the viewpoint of rolling efficiency, the cumulative reduction rate of the laminated slab is preferably 95% or less.

[0215] [Rolling end temperature (FT): Above the Ar3 phase transformation point and below 1000℃]

[0216] If the rolling end temperature of the aforementioned hot rolling is lower than the Ar3 phase transformation point, ferrite will be formed, thus deteriorating the toughness. Furthermore, if the rolling end temperature is lower than the Ar3 phase transformation point, it becomes low-temperature hot rolling, which, from the viewpoint of diffusion bonding, deteriorates the bonding properties of the cladding steel. Therefore, the rolling end temperature is set above the Ar3 phase transformation point. Moreover, the rolling end temperature is preferably Ar3 phase transformation point +20°C or higher.

[0217] On the other hand, if the rolling end temperature exceeds 1000°C, deformation bands that serve as nucleation sites will not be introduced into the austenite grains, making it impossible to obtain fine bainite and martensite, thus degrading the toughness of the cladding steel plate. Therefore, the rolling end temperature is set to below 1000°C. Furthermore, the rolling end temperature is preferably below 980°C.

[0218] (The above process (A) (the accelerated cooling process after reheating))

[0219] In the process (A) above, after cooling, the material is then heated to 800°C to 1000°C and accelerated to a cooling stop temperature below 350°C from a temperature above the Ar3 phase transformation point of the base material at an average cooling rate of 1.0°C / s to 20.0°C / s.

[0220] Here, "temperature above the Ar3 phase transition point of the base material" refers to the temperature of the base material surface above the Ar3 phase transition point at the start of accelerated cooling.

[0221] It should be noted that the cooling after hot rolling and before reheating can be to room temperature (-5 to 50°C). In addition, the cooling rate at this time does not need to be specifically specified, but for example, it can be air cooling at 0.01 to 1°C / s.

[0222] [Reheating temperature: 800℃~1000℃]

[0223] If the reheating temperature of the rolled sheet having the base material and cladding material is below 800°C, the strength may be too high and the toughness may not be restored. Additionally, the bonding rate may sometimes decrease. Therefore, the reheating temperature is set to 800°C or higher. Furthermore, the reheating temperature is preferably 820°C or higher.

[0224] On the other hand, if the reheating temperature exceeds 1000°C, insufficient strength may result. Therefore, the reheating temperature is set to below 1000°C. Furthermore, the reheating temperature is preferably below 980°C.

[0225] [Cooling start temperature: above the Ar3 phase transition point]

[0226] The reheated steel sheet is cooled starting at a temperature above the Ar3 transformation point of the base material. Here, "temperature above the Ar3 transformation point of the base material" means that the surface temperature of the base material at the moment the accelerated cooling begins is above the Ar3 transformation point of the base material. When the cooling start temperature is below the Ar3 transformation point of the base material, excessive ferrite is formed and coexists with martensite or bainite, which have large strength differences. As a result, the base material has insufficient strength and deteriorated toughness. Therefore, the cooling start temperature after reheating is set above the Ar3 transformation point. Furthermore, the cooling start temperature is preferably above the Ar3 transformation point + 20°C. The Ar3 transformation point can be calculated using the following formula.

[0227] Ar3 (℃)=910-310×[C]-80×[Mn]-20×[Cu]-55×[Ni]-15×[Cr]-80×[Mo]

[0228] In the above formula, [M] represents the content (mass%) of element M in the steel plate (base material), and is set to 0 (zero) if it is not present.

[0229] [Average cooling rate of steel plate: 1.0℃ / s~20.0℃ / s]

[0230] Cooling at an average cooling rate of 1.0 °C / s or higher is an essential process for obtaining high-strength and high-toughness steel sheets. Rapid cooling achieves the strength-enhancing effect of phase transformation strengthening. When the average cooling rate is lower than 1.0 °C / s, the grain size of bainite and martensite increases, and ferrite and pearlite are formed, which may lead to insufficient strength and deterioration of toughness. Therefore, the average cooling rate is set to 1.0 °C / s or higher. Furthermore, the average cooling rate is preferably 1.5 °C / s or higher.

[0231] On the other hand, if the average cooling rate exceeds 20.0 °C / s, the volume fraction of martensite becomes too high, sometimes resulting in reduced toughness. Additionally, the bonding properties may sometimes decrease. Therefore, the average cooling rate is set to 20.0 °C / s or less. Furthermore, the average cooling rate is preferably 15.0 °C / s or less.

[0232] Here, the average cooling rate during accelerated cooling is calculated by dividing the difference (°C) between the cooling start temperature and the cooling stop temperature at the position of 1 / 2 thickness in the thickness direction of the base steel plate by the cooling time (s).

[0233] It should be noted that the cooling start temperature and cooling stop temperature at the 1 / 2 position of the plate thickness in the thickness direction of the base steel plate are obtained by measuring the surface temperature of the steel plate with a radiation thermometer and calculating the temperature at the 1 / 2 position using differential calculations. Furthermore, the cooling time is the time required to supply cooling water to the steel plate, which is the time required for the plate to reach the cooling stop temperature from the cooling start temperature at the 1 / 2 position.

[0234] [Cooling stop temperature: below 350℃]

[0235] In this invention, after reheating, cooling to a cooling stop temperature of 350°C or below under the aforementioned conditions allows bainite or martensite to form uniformly at a specified volume fraction up to the center of the base material. It should be noted that if the cooling stop temperature exceeds 350°C, excessive ferrite and pearlite structures are formed, leading to insufficient strength and deteriorated toughness. Therefore, the cooling stop temperature is specified to be 350°C or below. Preferably, the cooling stop temperature is 300°C or below.

[0236] On the other hand, there is no particular limitation on the lower limit of the cooling stop temperature; it can be room temperature, but from the point of view of production efficiency, it is preferred to be 100°C.

[0237] In addition, after the accelerated cooling in the above-mentioned process (A) reaches the cooling stop temperature, the cladding steel plate is further tempered at a temperature of 550°C to 700°C.

[0238] Tempering temperature: 550℃~700℃

[0239] In this invention, tempering is performed to restore the toughness of the base material. If the temperature during reheating after tempering exceeds 700°C on average (temperature at 1 / 2 the thickness of the steel plate), dislocation recovery occurs, and the strength of the base material may decrease. Therefore, the tempering temperature is set to 700°C or below. Preferably, the tempering temperature is 680°C or below.

[0240] On the other hand, if the average temperature of the steel plate during reheating after tempering is below 550°C, the base material may lack sufficient toughness. Therefore, the tempering temperature is set to 550°C or higher. Preferably, the tempering temperature is 600°C or higher.

[0241] (The above process (B) (accelerated cooling process))

[0242] In process (B) above, the material is accelerated from a temperature above the Ar3 phase transformation point at an average cooling rate of 3°C / s to 50°C / s to a cooling stop temperature below 500°C. Alternatively, after accelerated cooling, tempering is performed at a temperature below 700°C. Here, the temperature above the Ar3 phase transformation point of the material refers to the surface temperature of the material.

[0243] [Cooling start temperature: above the Ar3 phase transition point]

[0244] If the accelerated cooling initiation temperature is lower than the Ar3 phase transformation point, ferrite will form, thus deteriorating toughness. Furthermore, if the accelerated cooling initiation temperature is lower than the Ar3 phase transformation point, the bonding strength of the cladding steel will deteriorate from the viewpoint of diffusion bonding. Therefore, the accelerated cooling initiation temperature is set above the Ar3 phase transformation point. Preferably, the accelerated cooling initiation temperature is Ar3 phase transformation point +20°C or higher.

[0245] It should be noted that the cooling (accelerated cooling) here is preferably carried out immediately after hot rolling, without air cooling to room temperature or reheating the rolled plate to 800°C to 1000°C.

[0246] [Average cooling rate of steel plate: 3℃ / s~50℃ / s]

[0247] Cooling at an average cooling rate of 3°C / s or higher is an essential process for obtaining high-strength and high-toughness steel plates. Rapid cooling achieves the strength enhancement effect resulting from phase transformation strengthening. When the average cooling rate is lower than 3°C / s, the grain size of bainite and martensite increases, or ferrite and pearlite are formed, which may lead to insufficient strength and deterioration of toughness. Therefore, the average cooling rate is set to 3°C / s or higher. The average cooling rate is preferably 5°C / s or higher, and more preferably 10°C / s or higher.

[0248] On the other hand, if the average cooling rate exceeds 50°C / s, the volume fraction of martensite becomes too high, sometimes reducing toughness. Additionally, the bonding rate between the base material and the cladding material may decrease. Therefore, the average cooling rate is set to 50°C / s or less. Furthermore, the average cooling rate is preferably 45°C / s or less.

[0249] Here, the average cooling rate during accelerated cooling is obtained by dividing the difference (°C) between the cooling start temperature and the cooling stop temperature at the position of 1 / 2 thickness in the thickness direction of the base steel plate by the cooling time (s).

[0250] It should be noted that the cooling start temperature and cooling stop temperature at the 1 / 2 position of the plate thickness in the thickness direction of the base billet are obtained by measuring the surface temperature of the steel plate with a radiation thermometer and calculating the temperature at the 1 / 2 position using differential calculations. Furthermore, the cooling time is the time required to supply cooling water to the steel plate, which is the time required for the plate to reach the cooling stop temperature from the cooling start temperature at the 1 / 2 position.

[0251] [Cooling stop temperature: below 500℃]

[0252] In this invention, by cooling to a cooling stop temperature of 500°C or below under the above conditions, bainite or martensite can be formed uniformly at a specified volume fraction up to the center of the base material. If the cooling stop temperature exceeds 500°C, excessive ferrite and pearlite structures are formed, leading to insufficient strength and deterioration of toughness. Therefore, the cooling stop temperature is specified to be 500°C or below. The cooling stop temperature is preferably 300°C or below. It should be noted that when tempering, described later, is performed after the accelerated cooling process, the cooling stop temperature is preferably 300°C or below, and more preferably 280°C or below.

[0253] On the other hand, there is no particular limitation on the lower limit of the cooling stop temperature, which can be room temperature, but from the point of view of production efficiency, the lower limit of the cooling stop temperature is preferably 150°C.

[0254] Furthermore, after the accelerated cooling in step (B) reaches the cooling stop temperature, the cladding steel sheet can be tempered at a temperature below 700°C as needed. That is, as part of step (B), tempering can be omitted after the accelerated cooling, or tempering can be performed at a temperature below 700°C after accelerated cooling.

[0255] Tempering temperature: below 700℃

[0256] In this invention, tempering can be performed as needed to restore the toughness of the base material. If the temperature during reheating after tempering exceeds 700°C on average (temperature at 1 / 2 the thickness of the steel plate), dislocation recovery occurs, and the strength of the base material may decrease. Therefore, the tempering temperature is set below 700°C. Preferably, the tempering temperature is below 680°C.

[0257] On the other hand, if the reheating temperature during tempering is below 550°C (average temperature for steel plates), the toughness of the base material may be insufficient. Therefore, a tempering temperature of 550°C or higher is preferred. A tempering temperature of 600°C or higher is more preferred.

[0258] It should be noted that the temperature of the billet steel plate and the cladding steel plate in this invention refers to the temperature at 1 / 2 of the thickness of the base material. The temperature can be obtained by measuring the surface temperature of the steel plate using a radiation thermometer, for example, by differential calculation using a process computer.

[0259] By subjecting a blank steel sheet having the above-described composition and a cladding material to the above-described manufacturing conditions, a cladding steel sheet according to the present invention can be obtained. Thus, the high-strength cladding steel sheet according to the present invention possesses excellent low-temperature toughness, resistance to ammonia SCC, and excellent bonding properties.

[0260] It should be noted that in the manufacturing method according to the present invention, conventional methods can be used for items not described in this specification.

[0261] Example

[0262] Table 1 shows the chemical composition of the base material (the remainder being Fe and unavoidable impurities). In the table, steel grades A to O are inventive examples within the scope of this invention. On the other hand, steel grades P to AE are comparative examples where any one of the components is outside the scope of this invention.

[0263] Table 2 shows the chemical composition of the coating material (the remainder is Fe and unavoidable impurities). In the table, steel grades a to m are inventive examples within the scope of this invention. On the other hand, steel grades n to p are comparative examples whose PRE values ​​are outside the scope of this invention.

[0264] The blank spaces in Tables 1 and 2 indicate that the element is not present or is present as an unavoidable impurity.

[0265]

[0266]

[0267] Cladding steel sheets (No. 1 to 91) were manufactured using base metal slabs with the chemical compositions shown in Table 1 and cladding material slabs with the chemical compositions shown in Table 2, under the manufacturing conditions shown in Table 3. Test plates for joints were collected from the obtained steel sheets, and welded joints were fabricated. The welding method was TIG welding, with multiple layers of weld overlay performed from the base metal side to the cladding material side.

[0268] The slabs are assembled using one of the following methods: sandwich method, open method, or sacrificial material method. In Tables 3-1 and 3-2, the sandwich method involves stacking slabs in the following order from top to bottom: base material slab, cladding material slab, cladding material slab, base material slab; the open method involves stacking slabs in the following order from top to bottom: cladding material slab, base material slab; and the sacrificial material method involves stacking slabs in the following order from top to bottom: sacrificial material, cladding material slab, base material slab.

[0269] The obtained cladding steel plates were evaluated for strength and toughness, bonding rate, and resistance to ammonia SCC in a liquid ammonia environment. The test methods are as follows.

[0270] [Strength Characteristics]

[0271] The thickness of the cladding material side of the cladding steel plate was reduced, and test pieces No. 1B of JIS Z 2201 were collected from the entire thickness of the base material. Tensile tests were performed according to the procedures described in JIS Z 2241 (2022), and the yield strength YS (YP (lower yield point YP) when there is a yield point, and 0.2% endurance σ0.2 when there is no yield point) and tensile strength (TS) were determined. Then, steel plates with a tensile strength of 780 MPa or higher in the base material were evaluated as steel plates with excellent tensile properties.

[0272] [toughness]

[0273] To evaluate the toughness of the base metal of the cladding steel plate, V-notch test pieces according to JIS Z 2202 were collected, with the midpoint of the base metal thickness as the center in the thickness direction. Additionally, to evaluate the toughness of the welded joint of the cladding steel plate, V-notch test pieces according to JIS Z 2202 were collected from the weld heat-affected zone of the base metal of the cladding steel plate in the welded joint, with the midpoint of the base metal thickness as the center in the thickness direction. For each condition, three test pieces were subjected to Charpy impact testing at -40°C according to the guidelines of JIS Z 2242 (2023), and the absorbed energy was measured. Steel plates with absorbed energies of 47 J or higher from all three test pieces were then evaluated as having excellent toughness. It should be noted that the minimum absorbed energy of the three test pieces is recorded in Tables 3-1 and 3-2.

[0274] [Joint ratio]

[0275] The bonding ratio at the cladding steel plate interface was calculated as follows: After mirror polishing of the cross-section of the base material and cladding material containing the cladding steel plate, a 1.0 × 10⁻¹ mm region was observed using a scanning electron microscope (SEM) at 1000x magnification along randomly selected interface directions in 10 fields of view. The bonding interface length was determined through image analysis. Then, based on the measured total length and bonding interface length, the bonding ratio was calculated using the following formula.

[0276] Bonding rate (%): 100 × bonding interface length (mm) / total measurement length (mm)

[0277] Here, the joint interface length refers to the total length of the portion of the interface determined by image analysis to be free of both voids and oxides. Steel plates with a joint rate of 70% or higher are then evaluated as having excellent joint properties.

[0278] [Ammonia SCC Resistance]

[0279] The ammonia SCC resistance of this invention is evaluated by applying a potential to a test piece that has been stressed by four-point bending in a test solution.

[0280] Specifically, follow these steps.

[0281] The cladding steel sheet of this invention is used in a manner where the cladding material comes into contact with ammonia, etc. Therefore, firstly, a thickness reduction process is performed on the base material side of the cladding steel sheet, and test pieces with a thickness of 1.5–3.0 mm × 15 mm × 115 mm are collected from the cladding material portion. When the cladding material thickness exceeds 3.0 mm, test pieces with a thickness of 3.0 mm are collected from the side of the cladding material not bonded to the base material. The collected test pieces are ultrasonically degreased in acetone for 5 minutes. A stress of 100% of the actual yield strength YS of the base material corresponding to each test piece is applied to each test piece by a four-point bending test. The four-point bending test piece is placed in a test tank. Next, a solution of 2 L of liquid ammonia with a purity of 99.999% or higher, mixed with ammonium carbamate: 5.00 mass%, O2: 1.000 bar, and water: 0.10 mass%, is filled into the test tank. Specifically, a specified amount of ammonium carbamate and water were added to the test tank, and liquid ammonia was added after further blowing in O2 gas. The ratio of the impregnation liquid volume to the surface area of ​​the impregnated test piece, i.e., the specific liquid volume, was 42 mL / cm². Stirring during the test was performed continuously at 10 rpm using a stir bar located in the test tank. The test liquid temperature was set to 25°C. After adjusting the test liquid temperature to 25°C, the corrosion potential of the test piece was measured using a potentiostat. The potential measurement and application were performed using a three-electrode method, with platinum electrodes used for both the reference and counter electrodes. Once the potential stabilized one hour after the start of the corrosion potential measurement, a potential of +0.5V vs. Pt was applied to the test piece, and the impregnation test began. After 504 hours from the start of the impregnation test, the test piece was removed from the test tank. Corrosion products on the surface of the test piece were removed, and cracks were visually observed on the surface and cross-section to evaluate the cracks. In this embodiment, for one condition, nine test pieces were used for a 504-hour impregnation test. If two or fewer test pieces show cracks deeper than 1.5 mm, the test piece is considered to have good ammonia SCC resistance (○); if three or more test pieces show cracks, the test piece is considered to have poor ammonia SCC resistance (×).

[0282] The evaluation results are recorded in Table 3.

[0283]

[0284]

[0285] As shown in Table 3-1, all the invention examples possess a tensile strength of over 780 MPa, an absorbed energy of over 47 J in a Charpy impact test at -40°C, and a bonding rate of over 70% between the base material and the coating material. Furthermore, the invention examples exhibit excellent resistance to ammonia SCC.

[0286] In contrast, as shown in Table 3-2, No. 47 to 65 have at least one of the following properties: tensile strength (TS), low-temperature toughness, and ammonia SCC resistance, because any chemical component in the base material and the coating material is outside the scope of this invention.

[0287] In addition, although the chemical composition of the base material and the coating material in Nos. 66 to 91 is within the scope of this invention, the manufacturing conditions are outside the scope of this invention, therefore at least one of the tensile strength TS, low temperature toughness, bonding rate, and resistance to ammonia SCC is poor.

Claims

1. A cladding steel sheet having a cladding material on at least one side of a base material, The chemical composition of the base material, by mass%, contains: C: 0.030–0.150%, Si: 0.05–0.55%, Mn: 0.50–2.10%, P: less than 0.020%, S: less than 0.010%, Al: 0.018–0.070%, Ni: 0.30–2.20%, Ti: 0.005–0.020%, N: 0.0020–0.0080%, O (oxygen): less than 0.0050%, and the Ti / N ratio is 2.2–6.

5. It further contains one or more of the following: Cu: less than 0.50%, Cr: less than 1.60%, Mo: less than 0.60%, Nb: less than 0.030%, V: less than 0.100%, B: less than 0.0050%, and Ca: less than 0.0040%, with the remainder consisting of Fe and unavoidable impurities. In the coating material The PRE value shown in equation (1) is 15 or higher. The tensile strength of the base material is above 780 MPa. The base material absorbs over 47 J of energy in a Charpy impact test at -40°C. The bonding rate between the base material and the coating material is over 70%. PRE=Cr%+3.3Mo%+30N%-Mn%···(1) In formula (1), M% represents the content of element M in the coating material, in mass%, and elements not present are set to 0 (zero).

2. A welded joint, which uses the cladding steel plate as described in claim 1, The heat-affected zone of the weld absorbs more than 47 J of energy in a Charpy impact test at -40°C.

3. A method for manufacturing a cladding steel plate, which is the method for manufacturing a cladding steel plate as described in claim 1. The base material slab is heated to 900℃~1200℃ (surface temperature gauge) and then hot-rolled to a rolling finish temperature of 700℃ or higher (surface temperature gauge) to produce the base material slab. After heating the slab blank of the coating material, hot rolling is performed to produce the coating material blank. The laminated slab, formed by stacking the base material blank and the cladding material blank, is heated to 1000℃~1250℃ (surface temperature). Hot rolling with a cumulative reduction rate of 65% or more and a rolling end temperature above the Ar3 phase transformation point and below 1000℃ is carried out to manufacture rolled plates with base material and cladding material. The rolled plate is subjected to the following treatment (A) or (B). (A) After the hot-rolled plate is cooled, Reheat to 800℃~1000℃, Accelerated cooling is performed from a temperature above the Ar3 phase transition point of the base material at an average cooling rate ranging from 1.0℃ / s to 20.0℃ / s, down to a cooling stop temperature below 350℃. After the accelerated cooling, tempering is carried out at a temperature of 550°C to 700°C. (B) The hot-rolled plate is accelerated from a temperature above the Ar3 phase transformation point of the base material to a cooling stop temperature below 500°C at an average cooling rate of 3°C / s to 50°C / s, or further tempered at a temperature below 700°C after the accelerated cooling.

4. A method for manufacturing a welded joint, comprising welding the cladding steel plate as described in claim 1 under heat input conditions of 50 kJ / cm or less, thereby manufacturing the welded joint.

Citation Information

Patent Citations

  • JP1980030062B2